Livestock marketing strategies in the Tandam Hilir II Village Deli Serdang District - Sembiring, Iskandar; Patriani, Peni (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Tandam Hilir Dua Village is a sub-district of Hamparan Perak, Deli Serdang Regency, North Sumatra Province, Indonesia.The population of beef cattle in 2019 recorded 19,375 heads, 68 buffaloes, 15.987 goats and 24’090 sheep. Growing animal husbandry leaves various problems such as marketing strategies due to the unavailability of collectors or buyers on a sustainable basis for the marketing of products, especially sheep, goats and beef cattle. This Community Service aims to increase farmers' knowledge about livestock marketing strategies in Tandam Hilir II Village, Deli Serdang Regency. Community service is also expected by farmers in the village of Tandam Hili II to be agents of change to improve skills in reliable marketing strategies. The method used in the first community service program is to approach, interview and deepen problems and find solutions to problems. Second, using the discussion forum, counseling, guidance and training practices in preparing livestock business financial statements. Third is coaching for farmers and farmers to apply solutions that have been obtained from discussion forums and practice training that was carried out previously. The results that have been achieved today are based on observations after the service program, namely improving knowledge related to good ruminant livestock marketing strategies